Prevalence and contributing factors of depression, anxiety, and stress among medical students in Universiti Putra Malaysia, Serdang - Alawad, Tasneem Abdalgfar (2017)
Introduction: Depression, anxiety and stress have become increasingly important public health issue globally. The nature of the medical program makes medical students more vulnerable to mental health problems including, depression, anxiety and stress.